PENGEMBANGAN JAMU INSTAN KUNYIT ASAM BERBASIS EDUKASI PARTISIPATIF DI DESA SUMBER MAKMUR - Anny Sartika Daulay; Najhatus Syukriyyah Khaidir; Dwi Shahputri; Dinda Alvionita Lubis; Sri Handayani; Reza Widya Lubis (LPPI UMN AL WASHLIYAH, 2026)
Research and community service on the development of instant turmeric and tamarind herbal medicine using a participatory education approach in Sumber Makmur Village. It began with the fact that people still use traditional herbal medicine that requires a long boiling process, is not clean, and does not last long. This situation indicates the need for innovation in herbal medicine products that are more suited to the needs of the times, such as instant turmeric and tamarind herbal medicine, a herbal supplement in powder form that is easy to brew, clean, long-lasting, and packaged in a modern and attractive way. Turmeric (Curcuma longa) was chosen because it contains curcumin which functions as an anti-inflammatory, antioxidant, and antibacterial. On the other hand, tamarind (Tamarindus indica) has organic acids that are effective for facilitating digestion, refreshing the body, and helping maintain health naturally. This program applies the Participatory Action Research (PAR) method that emphasizes the active role of the community in every step, from problem identification, planning, training, to evaluation. Participatory education is carried out through socialization, group discussions, and workshops on making instant turmeric and tamarind herbal medicine